2011
DOI: 10.4103/0256-4947.77495
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of various clinico-morphological variants of cutaneous tuberculosis and HIV concurrence: a study from the Indian subcontinent

Abstract: BACKGROUND AND OBJECTIVES:There are few reports of cutaneous tuberculosis with immunosuppressed states such as HIV, use of immunosuppressants or malignancy. Diagnosis is thus difficult and despite scientific advances such as polymerase chain reaction, it is frequently missed. Although rare, given its worldwide prevalence and the rising incidence of HIV, it is important for clinicians to recognize the variants and promptly treat the patient.DESIGN AND SETTING:Retrospective study of all cases of cutaneous tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 6 publications
3
27
0
4
Order By: Relevance
“…In a study by Varshney et al ,5 the overall incidence of cutaneous tuberculosis was 0.7% (131 of 18 720 outpatients). The most common variants seen were scrofuloderma (36.5%), lupus vulgaris (31%), tuberculosis verruca cutis (12.9%), LS (11.4%), papulonecrotic tuberculids (3.8%), erythema nodosum (2.2%) and erythema induratum of Bazin (1.5%).…”
Section: Discussionmentioning
confidence: 92%
“…In a study by Varshney et al ,5 the overall incidence of cutaneous tuberculosis was 0.7% (131 of 18 720 outpatients). The most common variants seen were scrofuloderma (36.5%), lupus vulgaris (31%), tuberculosis verruca cutis (12.9%), LS (11.4%), papulonecrotic tuberculids (3.8%), erythema nodosum (2.2%) and erythema induratum of Bazin (1.5%).…”
Section: Discussionmentioning
confidence: 92%
“…However the rates of TB are expected to rise due to immigration from TB endemic countries, emergence of human immunodeficiency virus infection (HIV) and the increase in use of immunosuppressive treatments. This can be seen in a study by Varshney et al, which reports that the overall incidence of cutaneous manifestations of TB was found to be 0.7% (131 of 18,720 patients), slightly higher than the incidence demonstrated in other studies from India [1]. The incidence of lichen scrofulosorum (LS), a tuberculid and therefore a form of CTB, varies between 2% and 11.4% in different studies among the cases of CTB but it has been reported as high as 23.5% to 33% in children [1,2].…”
Section: Introductionmentioning
confidence: 71%
“…Seven per cent of CTB patients were found to have LS in a prospective study in India [4]. Furthermore 11.4% of concurrent TB and HIV infection presented with LS in another Indian study [1]. LS could be a cutaneous sign for an underlying TB anywhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 40 years, additional descriptive terms have been employed, including nodules, ulcers, abscesses, papules, papulonecrotic discrete lesions or vulval hypertrophy and edema. To date, most of the described vulval histomorphology has focused on classic TB or tuberculous hypersensitivity responses [36][37][38][39][40][41][42][43][44][45][46].…”
Section: Glands (Eg) (A) (Hematoxylin and Eosin) Dilated Lymphatic (mentioning
confidence: 99%